Schaum's Statistics Supplementary Problem 9.31 : Confidence Interval for a Proportion - Rader, David (McGraw-Hill's AccessEngineering, 2020)
This video demonstrates the construction of confidence intervals for a proportion of a population using sample proportions. We assume a large population with the sample drawn with replacement.